Study of the oxygen role in the photoluminescence of erbium doped nanocrystalline silicon embedded in a silicon amorphous matrix - Cerqueira, M. F. (2006)
We have produced and studied erbium doped nanocrystalline silicon thin films with different oxygen and hydrogen content in order to evaluate the influence of the matrix on the Er3+ emission and on the 0.89 eV and 1.17 eV bands. Films were grown by reactive magnetron sputtering on glass substrates under several different conditions (RF power, Er content and gas mixture composition) in order to obtain different microstructures. The structural parameters and the chemical composition of the samples were obtained by X-ray in the grazing incidence geometry, Raman spectroscopy and Rutherford back scattering analysis. Using X-ray technique combined with Raman spectroscopy information on the crystalline fraction and the average crystallite size of Si nanocrystals was obtained. Dependence of the 0.89 eV and 1.17 eV peaks in Si heterogeneous matrixes on the films crystallinity and O/H ratio has been analyzed